Somatostatin and Corticotrophin Releasing Hormone Cell Types Are a Major Source of Descending Input From the Forebrain to the Parabrachial Nucleus in Mice - Magableh, Ali (Oxford University Press, 2014)
The pontine parabrachial nucleus (PBN) receives substantial descending input from higher order forebrain regions that exerts inhibitory and excitatory influences on taste-evoked responses. Somatostatin (Sst) and corticotrophin releasing hormone (Crh) reporter mice were used in conjunction with injection of the retrograde tracer CTb-488 into the caudal PBN to determine the extent to which Sst and Crh cell types contribute to the descending pathways originating in the lateral hypothalamus (LH), central nucleus of the amygdala (CeA), bed nucleus of the stria terminalis (BNST), and insular cortex (IC). Five to 7 days following injections, the animals were euthanized and tissue sections prepared for confocal microscopy. Crh cell types in each forebrain site except IC project to the PBN with the greatest percentage originating in the BNST. For Sst cell types, the largest percentage of double-labeled cells was found in the CeA followed by the BNST. Few retrogradely labeled cells in the LH coexpressed Sst, whereas no double-labeled cells were observed in IC. The present results suggest that Sst and Crh cell types are a substantial component of the descending pathways from the amygdala and/or BNST to the PBN and are positioned to exert neuromodulatory effects on central taste processing.